Microalbuminuria in healthy kidney donors in pre transplant donor evaluation - Anusha Kumari; Ejaz Ahmed; Amara Naseer; Anmol Shankar (Journal of the Pakistan Medical Association, 2026)
Objectives: To determine the frequency of abnormal microalbuminuria in healthy kidney donors undergoing pre-transplant evaluation. Method: The analytical cross-sectional study was conducted from January to June 2025 at the Sindh Institute of Urology and Transplantation, Karachi, and comprised living healthy prospective kidney donors aged 20-60 years. Clinical assessment and laboratory analysis of donors were performed, with quantitative variables being age, total protein excretion and albumin excretion, and qualitative variables being gender, smoking status, abnormal proteinuria and abnormal albuminuria. Abnormal albuminuria was established as albumin-to-creatinine ratio >30mg/g. Data was analysed using SPSS 25. Results: Of the 195 donors with mean age 41.6+9.8 years, 112(57.4%) were females. The median excretion of 24-hour urinary protein was 107mg/day (interquartile range: 95-230mg/day), and donor’s overt proteinuria was detected in 37(18.9%). Normal albumin excretion rates were found in 123(63.1%) subjects, and abnormal albuminuria occurred in 72(36.9%). Microalbuminuria was present in 49(25.1%) of the donors, while macroalbuminuria was found in 23(11.8). Age >40 years (p=0.021) and overweight/obesity (p=0.011) were significantly associated with abnormal albuminuria. Conclusion: Abnormal albuminuria affected donor eligibility in older age and with higher body mass index. Incorporation of albumin-to-creatinine ratio into routine donor assessment enhanced risk stratification capability. Key Words: Albuminuria, Body mass index, Donor screening, Kidney donation, Microalbuminuria.